Genome-Wide Association Study-Based Identification of SNPs and Haplotypes Associated With Goose Reproductive Performance and Egg Quality - Gao, Guangliang; Gao, Dengfeng; Zhao, Xianzhi; Xu, Songsong; Zhang, Keshan; Wu, Rui; Yin, Chunhui; Li, Jing; Xie, Youhui; Hu, Silu; Wang, Qigui (Frontiers in Genetics, 2021)
Geese are one of the most economically important waterfowl worldwide. With the increasing public concern surrounding animal health and the regulation of the goose rearing industry, reproductive performance and egg quality have become a major focus for researchers. To promote the accuracy of selective breeding and identify important candidate genes associated with reproductive performance and egg quality traits, we examined the birth body weight (BBW), egg number at 48 weeks (EN48), egg number at 60 weeks (EN60) and egg yolk color (EYC) among 209 Sichuan White geese using a genome-wide association study (GWAS). In this study, we obtained 2.896 Tb of raw whole-genome sequencing data with a mean depth coverage of 12.44. A total of 9,279,339 single nucleotide polymorphisms (SNPs) were identified in the goose genome. The GWAS analysis showed that 26 SNPs were significantly associated with the examined birth body weight (BBW), egg number in 48- and 60-week-old geese (EN48 and EN60) traits and egg yolk color (EYC), respectively. Notably, two genomic regions, a 28.85 kb genomic region (4512855bp ~ 4541709bp) on chromosome 35, and 294.57kb genomic region (21069009 b ~ 21363580 bp) located on chromosome 5, were significantly associated with egg number in 48- and 60-week-old geese (EN40 and EN60), and egg yolk color (EYC), respectively. In addition, we performed the MALDI-TOP MS method to detected SNPs and haplotypes markers for EN48, EN60 and EYC traits were identified in the candidate gene TMEM161A, CALCR, TFPI2, and GLP1R, respectively. The SNPs, haplotypes markers and genes identified in this study can be used for marker-assisted selection of reproductive performance and egg quality traits in geese, promoting the accuracy of selective breeding, providing a foundation for a better understanding of the mechanisms underlying reproduction and egg quality in geese.